A critical analysis of national dementia plans: comparison of preventive strategies in five European countries - Blandi, Lorenzo; Clemens, Timo; Gentile, Leandro; Vecchio, Riccardo; Brand, Helmut; Odone, Anna (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Preventive measures can avert up to 45% of dementia cases worldwide. The aim of the study is to analyse some selected national dementia prevention strategic plans. Methods. A qualitative comparative analysis was performed between national dementia plans of the European countries with the best healthy life expectancy among the elderly. The national dementia plans of France, Ireland, Italy, Spain and Sweden were included. The consensus on priority actions and key elements of prevention policies was evaluated, according to the World Health Organization recommendations and to an analysis tool designed for evaluating chronic diseases policies. Results. All the countries emphasized the importance of prevention policies within their dementia plans and established monitoring committees. However, not all countries defined timelines for policy implementation and only Spain updated its national plan so far. The integration of dementia prevention with other chronic disease preventive campaigns is still lacking, and also a clear allocation of funds for dementia plans is absent so far. Conclusions. All countries extensively followed the World Health Organization’s recommendations. However, the plans have not been updated. Thus, they do not address all the current known risk factors for dementia, preventing only a fraction of potentially preventable cases. Moreover, the need for financial support in national dementia plans are critical but inadequately addressed, with inconsistent or undefined funding sources to implement their goals.